UTILIZATION OF IJUKâS FIBER AS MATERIAL OF PARTICLEâS BOARD - Hidayah, Annisa Nurul; Sari, Ayu Mustika (Jurnal Indonesia Emas PPI Dunia, 2018)
The particle board is an artificial board that uses a mixture of organic adhesives.This board is one of alternative ways because use ijukâs fiber as the material which mixed with plastic waste matrix of glass mineral water. The purpose of this experiment was to compare the particle physics of the particle board, on parameter comparison (Jappanese Standard Associaton (JIS) A 5908-2003 and Indonesian National Standard (SNI) 03-2105-1996.The method used consisted of the process of preparation of tools and materials, weighing matrix and ijukâs fiber, particle printing using hotpress machine, cooling and testing of board characteristics include density, water absorption and thickness development Based on experimental particle board materials obtained density ranges from 0.50 - 0.90 gram / cm3, water absorption 16.38% - 18.63% for 1: 4 and 7.76% - 13.99% for 1: 5 material comparison and thickness development 0.00% - 8.20% for material comparison 1: 4 and 0.56% - 2.60% for 1: 5 material comparison.